Riddle of the Sphinx: Emerging Role of Transfer RNAs in Human Cancer - Qiu, Zhilin; Wang, Qin; Liu, Lei; Li, Guozheng; Hao, Yi; Ning, Shipeng; Zhang, Lei; Zhang, Xin; Chen, Yihai; Wu, Jiale; Wang, Xinheng; Yang, Shuai; et al. (Frontiers in Pharmacology, 2021)
The dysregulation of transfer RNA (tRNA) expression contributes to proteome diversity, cell population heterogeneity, and genome instability, which may be associated with susceptibility to human cancer. However, the relationship between tRNA dysregulation and cancer susceptibility remains elusive because the landscape of cancer-associated tRNAs has not been portrayed yet. Furthermore, the molecular mechanisms of tRNAs involved in tumorigenesis and cancer progression have not been systematically understood. In this review, we provide a detailed account of the current knowledge on tRNAs associated with cancer and comprehensively summarize the basic characteristics and functions of these tRNAs, with a special focus on their role and involvement in human cancer. This review bridges the gap between tRNAs and cancer and broadens our understanding of their relationship, thus providing new insights and strategies to improve the potential clinical applications of tRNAs for cancer diagnosis and therapy.